Hepatic artery infusion chemotherapy with systemic capecitabine and camrelizumab for treating unresectable hilar cholangiocarcinoma: An initial investigation of efficacy and safety - Li, Long; Liu, Song; Wang, Qingdong; Wang, Yanhua; Yu, Guangji (Journal of cancer research and therapeutics, 2024)
ABSTRACT Objective: This study aimed to evaluate the efficacy and safety of sequential treatment of continuous transcatheter hepatic artery infusion chemotherapy (HAIC) with systemic capecitabine monotherapy and camrelizumab for treating unresectable hilar cholangiocarcinoma (HCCA). Methods: This study retrospectively analyzed patients with unresectable HCCA admitted to Linyi Cancer Hospital in Shandong Province from October 2019 to December 2021. All enrolled patients were treated with HAIC (mFOLFOX7) + camrelizumab for 2-6 cycles and administered systemic therapy with capecitabine and camrelizumab. The objective response rate (ORR), disease control rate (DCR), and adverse reactions of patients were assessed. The Kaplan-Meier method was used to describe overall survival (OS), and univariate and multivariate Cox regression models were utilized to analyze the influencing factors of OS. Results: This study included 34 patients, ORR was 61.76% (21/34), and DCR was 97.06% (33/34) after two HAIC cycles. The median follow-up time was 17.5 months, with an average of 18.32 ± 8.06 months, and the median OS was 20.0 months. HAIC-related adverse reactions included mainly gastrointestinal symptoms and hematological toxicity caused by chemotherapy drugs, all of which were grades 1-2. Further, adverse events for camrelizumab treatment included fatigue, skin rash, and hypothyroidism, all of which were grade <3. Cox regression analysis revealed that the periductal infiltrating type of growth pattern indicated a worse OS, whereas more HAIC cycles (5 ~ 6) were a protective factor for OS. Conclusion: HAIC sequentially combined with systemic capecitabine chemotherapy and a programmed death-1 inhibitor displayed favorable effects for unresectable HCCA, with controllable adverse reactions.